Pathogen-Informed Strategies for Durable Resistance in Rice: Lessons from Bacterial Blight - Lore, Jagjeet S.; Pinili, Dale; Bhatia, D.; Balloyan, Lemuel Ray; Navea, Ian Paul; Hunjan, Mandeep S.; Mangat, Gurjit S.; Singh, Ram; Platten, John Damien; Yang, Bing; Leach, Jan E.; White, Frank F.; et al. (Annual Reviews, 2025)
Bacterial blight (BB), caused by Xanthomonas oryzae pathovar oryzae (Xoo), is a major rice disease in Asia and Africa. Xoo possesses virulence factors for pathogenicity and race differentiation that complicate resistance breeding of rice. The availability of 48 BB resistance (R) genes (Xa/xa) portends the selection of R genes for broad and durable resistance. To establish durable resistance, understanding the pathogen virulence spectrum and host resistance mechanisms is required. This review examines the global distribution and diversity of Xoo populations, highlights the different resistance mechanisms of 15 Xa/xa genes, and identifies the three effective resistance genes for 24 countries. The review proposes strategies for durable, broad-spectrum resistance to BB.